Quarrying and Sustainability during Urbanazion: Gebze District Case - Ertan Mert; Zeynep Gamze Mert (European Regional Science Association (ERSA), 2011)
The requirement of construction materials increases along with the developing urbanization. Despite the most of quarries are established in rural or semi rural areas, their locations remain in or close to the urban areas in parallel with the expansion of residential areas in proportion to the rate of urbanization. Continuing population growth, social, industrial and economic developments require more construction materials. Gebze region uses approximately 8,000,000 tons of aggregate per year for construction sector. The present quarries are planned to be abandoned in the following years. Regardless of potential problems, it is important for planning to estimate future recources. Nowadays there are public housing, organized industrial zones and highway projects at planning and construction stages. Nevertheless, Ballıkayalar National Park is close to likely potential material quarries. By avoiding the national park area, the availability and the quality of materials should be established at an early stage, as material production and transportation costs can be an important consideration when selecting a design solution.
Keywords: 330